The cost of delivering COVID-19 vaccines in four districts in Malawi - Anika Ruisch; Simon Ntopi; Ishani Mathur; Maeve Conlin; Anna McCaffrey; Damian G. Walker; Christian Suharlim (Cost Effectiveness and Resource Allocation)
Abstract While COVID-19 vaccines became available in late 2020, low-income countries (LICs) faced challenging COVID-19 vaccine distribution efforts in terms of both a delayed and scarce vaccine supply and barriers reaching the target populations. The cost of delivering COVID-19 vaccines in LICs is uncertain, which complicates planning and budgeting for country leadership as well as major funders. In the absence of such data, a global model was developed by the COVAX Working Group on Delivery Costing using data on the costs of similar immunization campaigns and assumptions. This study has two objectives, firstly to estimate the costs of delivering COVID-19 vaccine delivery using primary data collected in Malawi, and secondly comparing these estimates to modeled estimates based on secondary data, to contribute to a growing evidence base on the cost of the COVID-19 vaccination delivery in LICs. This retrospective study used a bottom-up method to estimate the financial and economic costs. Data were collected from health facilities and health posts via a COVID-19 cost survey. The data sources included existing records and interviews with relevant districts and facility staff. Twenty representative vaccine delivery sites were purposively selected across four districts. We focused on major cost drivers that contributed to the highest proportion and variability in delivery costs. The total financial cost of COVID-19 vaccine delivery in 20 facilities across four districts in Malawi (from April 1, 2021–March 31, 2022) was US$ 322,786. During that period, the 20 facilities delivered 70,947 vaccines. The financial cost per dose delivered was US$ 4.55. Considering the reallocation of existing staff time toward COVID-19 vaccination, volunteer opportunity costs, and donated vehicles, the economic cost per dose delivered was nearly four times greater at US$ 16.15. The economic cost of labor was estimated at US$ 10.75 per dose delivered and accounts for two-thirds of the total economic cost. This study is the first to provide evidence on the cost of COVID-19 vaccine delivery in Malawi. The financial cost of delivering the COVID-19 vaccine in twenty health facilities across 4 districts in Malawi, at US$ 4.55 [US$ 3.23– US$ 6.33] per dose delivered. We observed a large amount of labor reallocation towards COVID-19 vaccination.